Necrotic and Cytolytic Activity on Grapevine Leaves Produced by Nep1-Like Proteins of Diplodia seriata - Cobos, Rebeca; Calvo-Peña, Carla; Álvarez-Pérez, José Manuel; Ibáñez, Ana; Diez-Galán, Alba; González-García, Sandra; García-Angulo, Penélope; Acebes, Jose Luis; Coque, Juan José R. (Frontiers in Plant Science, 2019)
Many phytopathogenic fungi produce necrosis and ethylene inducing peptide 1 (Nep1-like proteins or NLP) that trigger leaf necrosis and the activation of defense mechanisms. These proteins have been widely studied in plant pathogens as Moniliophthora perniciosa or Botrytis cinerea between others, but little is known about their biological roles in grapevine trunk pathogens. Advances in the sequencing of genomes of several fungi involved in grapevine trunk diseases have revealed that these proteins are present in several copies in their genomes. The aim of this project was to analyze the presence of genes encoding NLP proteins in the Diplodia seriata genome and to characterize their putative role as virulence factors associated to grapevine trunk diseases. In this study, we characterized four NLPs from Diplodia seriata. All proteins showed highly similar amino acid sequences and contained the characteristic peptide motifs of NLPs. DserNEPs slightly reduced the viability of Vitis vinifera L. cell cultures. The cytolytic activity from DserNEP1 was stronger than that from DserNEP2, even at low concentrations. Purified DserNEPs also produced necrosis in leaves when they were inoculated into micro propagules of V. vinifera L. This is the first record of Nep1-like proteins from a fungus associated with grapevine trunk diseases and also from a member of the Botryosphaeriaceae family.